Toxicity outcome of concurrent teletherapy and brachytherapy compared with teletherapy followed by brachytherapy in locally advanced carcinoma cervix - Sharmin, Sadia; Bari, M. Abul; Ruma, Rokaya Sultana; Anika, Afsana Sharmin; Shimul, Ashiqur Rahman (International Journal of Research in Medical Sciences, 2022)
Background: Teletherapy and intracavitary brachytherapy are definitive treatment modalities for stages IIB to IVA cervical carcinoma. Globally, it is the second most common cancer among female. Majority of patients attend the hospital with locally advanced stage due to less screening facility and social stigma. Methods: This quasi-experimental study was conducted from January 2019 to June 2020 with a total of 76 patients. The patients were equally divided into two groups: A and B after obtaining their informed written consent. Results: Final follow up was given after completion of treatment at 24 weeks. Patients in both groups developed grade 1 gastrointestinal and genitourinary toxicities (10.5% versus 13.1%, 13.1% versus 15.7% in group A and B respectively). Two patients in group A and three patients in group B developed grade 2 gastrointestinal toxicities. In genitourinary toxicities, grade 2 toxicities were observed in two patients of group A and four patients of group B, (p>0.05). None developed grade 3 and 4 gastrointestinal and genitourinary toxicities. There were no statistically significant variations in treatment related toxicities between the two groups. Conclusions: Both gastrointestinal, genitourinary toxicities were comparable between two groups. The toxicities were acceptable and well tolerated.